DANA OTONOMI KHUSUS PADA SEKTOR PENDIDIKAN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA DI KABUPATEN MERAUKE - Nur Jalal; Hendricus Lembang (Universitas Musamus, Merauke, Papua, 2017)
Special autonomy is a form of delegation of powers and lokal governance broadly with respect to the condition of the area is expected to accomodate in this regard special attention to endogenous people. Therefore, in order to support and to finance development granted special autonomy funds. The objective of this study is to provide a general overview of the development of Human Resources in Merauke and scrutinese data and potential human resource issues by formulating policy strategy. That can be through aquity strategy, expanding access, promoting quality, relevance and competitiveness, and also the strengthening of administrative governance and accountability. It takes accelerated achievement by providing greater opportunities especially those who have never attended formal education schools through the path of non-formal education services, sustained by the education budget from special autonomy grant. This research type is a qualitative-descriptive analysis techniques through observation and interviews.